Retraction: Long non-coding RNA PVT1 facilitates cell proliferation by epigenetically regulating FOXF1 in breast cancer. Issue 39 (5th September 2022) - Guo, Guangcheng; Wang, Fang; Han, Mingli; Gu, Yuanting; Duan, Xin; Li, Lin
Abstract : Retraction of 'Long non-coding RNA PVT1 facilitates cell proliferation by epigenetically regulating FOXF1 in breast cancer' by Guangcheng Guo et al., RSC Adv., 2018, 8, 2740–2750, ; https://doi.org/10.1039/C7RA12042G .